GIS-Based Decision Support System and Analytical Hierrachical Process for Integrated Flood Management - Salim Mohammed Al-Waili, Zulkiflee Abd Latif, Siti Aekbal Salleh (International Journal of Intelligent Systems and Applications in Engineering, 2023)
Massive flood losses have prompted initiatives to reduce flooding all around the world. Flood risk assessment methods that are widely used nowadays include remote sensing and Geographic Information Systems (GIS). Both of these systems provide integrated models for analyzing flood risk. Web-based geographic information systems are superior to desktop GIS for doing real-time analyses of flood risk. The Wadi Aday Basin in Oman is going to be evaluated using a web-based geographic information system (GIS), which is the purpose of this project. Cities, location, census statistics, land use and land cover, road network, structures, flood risk management, wadi spread, geomorphology, and the boundaries of the study region are all things that will be discussed. Features such as zooming in and out, measuring features, managing layers, adjusting the level of transparency, and querying geographical data are all provided. A QGIS web-based GIS was designed for the Wadi Aday Basin in the Sultanate of Oman to evaluate and map the regions prone to flooding. The analytical hierarchical process (AHP) technique was applied where it provides a systematic approach for combining the impact of multiple thematic levels to obtain qualitative and quantitative information on successful mitigation of flood risks. The specifics of this information are explained in the article. In order to create a comprehensive Flood Risk Map, the relevant thematic data are brought together in a GIS setting. The AHP approach is used to calculate the flood hazard index, and this index not only takes into account the likelihood that each location will be flooded, but it also takes into account the overall influence that each of the themes has on the flood risk zonation.